Attitudes Towards Women's Participation in Local Politics in South Asia. Issue 1 (2nd January 2020) - Haug, Marit; Aasland, Aadne; Aasen, Berit
Abstract: Despite men's traditional dominance in politics, survey data from selected geographical areas in India, Nepal and Bhutan show that attitudes towards women's participation in local politics are overwhelmingly positive. Attitudes cluster along three major dimensions: perceptions of women's capacities to join politics, the consequences of political engagement for the family's reputation, and consequences of women's political participation for their domestic responsibilities. Households with high economic status and political leaders are more positive whilst education, organisational membership, and living in urban areas do not show a consistent effect across the three dimensions, so we do not find a 'modernity effect'. Despite variations in where and how women participate and in socio-economic and cultural contexts, attitudes are consistently positive, indicating that explanations for attitudinal changes are varied and complex. Nepal's high score may be due to the political, social and military mobilisation in the last generation, while it is likely that reservation in India and women's relative equality in Bhutan have contributed towards positive attitudes. Data are drawn from a survey of 6647 local level politicians, civil society leaders and ordinary citizens, and from interviews.